New keys for old locks: carborane-containing drugs as platforms for mechanism-based therapies. (19th June 2019) - Stockmann, Philipp; Gozzi, Marta; Kuhnert, Robert; Sárosi, Menyhárt B.; Hey-Hawkins, Evamarie
Abstract : Carborane derivatives as a new class of drugs ("new keys") for important receptors ("old locks") as targets for efficient therapeutic treatments. Abstract : Icosahedral carboranes in medicine are still an emerging class of compounds with potential beneficial applications in drug design. These highly hydrophobic clusters are potential "new keys for old locks" which open up an exciting field of research for well-known, but challenging important therapeutic substrates, as demonstrated by the numerous examples discussed in this review.